Pitfalls and recommendations in cases of laser removal of decorative tattoos with pigmented lesions: case report and review of the literature - Pohl, Laura; Kaiser, Kathrine Eve; Raulin, Christian (JAMA dermatology, 2013)
Pigmented lesions in decorative tattoos cause diagnostic difficulties at a clinical and dermoscopic level. In cases of laser removal of tattoos, hidden suspicious nevi may be revealed gradually.We describe the first case of a malignant melanoma that developed on a preexisting nevus within a tattoo during and between the phases of laser removal. The patient refused to undergo excision of the nevus until we made excision conditional for continued laser treatment.The English literature reports 16 cases of malignant melanoma developing in tattoos. Correlation between the placement of tattoos and the development of malignant melanoma remains unclear. Our case emphasizes the diagnostic problems of pigmented lesions within tattoos. For safety reasons, tattoos should never be placed on pigmented lesions; if they are, the tattoos should not undergo laser treatment. We suggest an excision before starting laser tattoo removal. Dermoscopic assessments on a regular basis during the period of tattoo removal are recommended.
Gesehen am 03.12.2021